ANALISIS NILAI KEHIDUPAN PADA FILM KELUARGA CEMARA SUTRADARA YANDY LAURENS DAN IMPLIKASI TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - Roy Efendi; Frida Rosamy Najjah; Siti Chodijah (Triangulasi: Jurnal Pendidikan Kebahasaan, Kesastraan, Dan Pembelajaran, 2023)
A film can be used as a learning material to analyze the various values contained in a film and it is expected that positive values in the film can be a mirror in everyday attitudes and behavior. Value as a guide and handle. Values are used for a reason, basis, or foundation or motivation in determining attitudes and actions. The film of Keluarga Cemara contains moral messages and life values. The film Keluarga Cemara tells the story of a nuclear family who lives in the city of Jakarta and needs to deal with a situation where their possessions are depleted due to being lied to by one of their extended family members. The film Keluarga Cemara shows how parents educate their children, the family can accept all conditions, and how children in social relationships and adapt to the environment. This study aims to identify and describe the values of life in the film Keluarga Cemara and its implications for learning Indonesian in high school. The method used in this study is the qualitative descriptive method. The Data used in this study is in the form of a dialogue between characters in the film family. Checking the validity of the data in the study using the triangulation method. The value of life that became the focus of research, namely the value of compassion, the value of wisdom, the value of justice, moral values, and the value of life from the results of the study were found in as many as 19 quotes from the value of compassion, 12 quotes the value of responsibility, 3 quotes moral values, 1 quote the value of justice, and 3 quotes the value of wisdom. With the results of triangulation, as much as 100% of the interviewees agreed with the results of the researcher's analysis. The results of this study deserve to be used as teaching materials for learning the Indonesian language and literature.